1998
DOI: 10.1183/09031936.98.12040935
|View full text |Cite
|
Sign up to set email alerts
|

Validation of respiratory inductive plethysmography using the Qualitative Diagnostic Calibration method in anaesthetized infants

Abstract: During recent years there has been renewed interest in noninvasive methods of assessing respiratory function in infants, since the use of face masks and pneumotachographs (PNT) have both been shown to affect breathing pattern [1]. Respiratory inductive plethysmography (RIP) is a means of measuring breathing movements without any connections at the airway opening, and therefore has numerous potential applications in infants, including prolonged respiratory monitoring in the intensive care unit or postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
68
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 29 publications
(53 reference statements)
7
68
0
Order By: Relevance
“…Unfortunately, the calibration procedure is critical and patient-dependent. In addition, measurements are not reliable if the position and condition of the patient differ from those assumed during calibration (3). Moreover, the use of RIP for tracking longterm changes in EELV is still questioned (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the calibration procedure is critical and patient-dependent. In addition, measurements are not reliable if the position and condition of the patient differ from those assumed during calibration (3). Moreover, the use of RIP for tracking longterm changes in EELV is still questioned (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Connecting to the airway opening may introduce leaks, annoy the infant, and affect the breathing pattern (1,2), while the use of patient-dependent calibration procedures can lead to inaccurate measurements when a patient's condition or posture changes with respect to the baseline state (3). Moreover, none of the existing techniques have proved to be reliable in tracking long-term changes in endexpiratory lung volume (EELV) due to integration drift or problems in the measurements stability (4,5).…”
mentioning
confidence: 99%
“…They do not rely on a calibrated RIP system. The calibration routines which assign proportionality constants to the ribcage and abdomen signals, thereby allowing their summation to give a tidal volume, 13,[34][35][36] assume a fixed spinal angle, an assumption that is problematic with mobile infants, postanesthesia. The algorithms do not require segmentation of the data record into individual breaths.…”
Section: Discussionmentioning
confidence: 99%
“…(11) According to the authors, the contributions of the rib cages and abdomens of anesthetized children were insufficient to derive K. One of the findings of the present study was the contribution of the rib the gold standard method (ISOCAL), various studies have suggested the use of the QDC method. (11)(12)(13)(14) One of the major advantages of the QDC method is that it is easy to perform, given that, for QDC, individuals need only maintain baseline breathing for 5 min, and calibration is performed on the basis of the variation in the results obtained for each compartment. This method is questionable in view of the RIP calibration principle, i.e., variation in calibration because of volume shifts between the rib cage and abdomen.…”
Section: Discussionmentioning
confidence: 72%
“…(4,8,9) Although ISOCAL is considered the gold standard for RIP calibration, the vast majority of studies employ QDC because the method requires no specific respiratory maneuvers. (10)(11)(12)(13) We are unaware of any studies comparing the two methods of RIP calibration regarding the values of the constant K when different positions are employed. …”
mentioning
confidence: 99%